Geography of innovative activities in the andalusian aeroespace cluster. - López-Otero, Javier (Revista de Estudios Andaluces, 2014)
This paper aims at analyzing innovation in corporarions located within the so called innovation areas. Namely it will be studied wether there are significative differences in terms of innovation between firms located inside and outside innovation areas. Furthermore, it have been studied which factors might have the strongest effect on the attraction of innovative firms